P301 Ustekinumab improves health-related quality of life in patients with moderate-to-severe Crohn's disease: results up to Week 48 of the STARDUST trial. (27th May 2021) - Danese, S; Vermeire, S; D'Haens, G; Panés, J; Dignass, A; Magro, F; Nazar, M; Le Bars, M; Lahaye, M; Ni, L; Bravatà, I; Gaya, D R; et al.
Abstract: Background: A treat-to-target (T2T) strategy may optimize inflammatory bowel disease management. The STARDUST trial compared a T2T maintenance strategy against standard of care (SoC) in Crohn's disease (CD) patients treated with ustekinumab (UST). The primary endpoint, safety, and efficacy data of STARDUST have been published previously. 1 Here we present results for health-related quality of life (HRQoL) measures and impact of UST on work and activities at Week (W)48 of UST maintenance, comparing T2T and SoC. Methods: Adult patients with moderate–severely active CD received iv, weight-based UST ~6 mg/kg at W0 (baseline [BL]); then SC UST 90 mg at W8. At W16, CD activity index (CDAI) 70 responders were randomized (1:1) to either T2T (maintenance dosing, q12w or q8w, assigned based on endoscopic activity and further dose escalations up to q4w if clinical and biomarker-directed targets were not met) or SoC (maintenance based on EU SmPC; q12w or q8w based on clinical judgement). In this analysis we assessed changes from BL in the following HRQoL measures at W48: Inflammatory Bowel Disease Questionnaire (IBDQ), EuroQoL 5 Dimension 5 Level (EQ-5D-5L), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) tools, and Hospital Anxiety and Depression Scale – anxiety and depression subscales (HADS-A and -D) alongside the Work Productivity and Activity Impairment (WPAI) questionnaire; time lost from work was also recorded. Percentage of patients with IBDQ response (16 point improvement from BL) and remission (IBDQ score ≥170) at W48 were also analysed. Results: Of 500 patients enrolled, 441 were randomized to T2T (n=220) or SoC (n=221); 79.1% and 87.3%, respectively, completed W48. At W48, the percentage of patients in T2T and SoC arms with IBDQ response (58.2% and 67.0%, respectively) and remission (45.0% and 53.4%, respectively) were similar (both p=ns). Similar changes from BL at W48 in IBDQ, EQ-5D-5L (visual analogue scale and index score), FACIT-F, HADS-A and -D and WPAI were noted in both treatment arms (Table 1). WPAI 7-Point Improvement from BL per domain at W48 are presented in Table 2. During the last 4 weeks preceding the visit at W48, patients in T2T and SoC arms on average lost 1.7 and 2.2 fewer days from work due to CD, respectively, compared to BL (p=ns). At W48, 62.3% and 72.3% were in employment in T2T and SoC arms, respectively (p=ns), compared to 61.8% and 63.5%, respectively at BL. Conclusion: UST treatment improved HRQoL and work productivity and helped decrease time lost from work in patients with moderate-to-severe CD, regardless of T2T or SoC strategy. Improvements were generally maintained up to W48. Reference: Danese S, et al. United European Gastroenterol J . 2020;8:1264–1265 (Abstract LB11).